Recent Advancement on Current Trend in The Management of Endocrine Emergency in Critically Ill Patient - Ferdous, HS; Afsana, Faria; Qureshi, Nazmulkabir; Rouf, Rushda SB; Parvez, AA; Mir, AS (Journal of Medicine, 2016)
Endocrine emergencies represent a group of potentially life-threatening conditions that are frequently overlooked, resulting in delays in both diagnosis and treatment, factors that further contribute to their already high associated mortality rates. Although endocrine emergencies are often encountered in patients with a known endocrinopathy, the emergency may be the initial presentation in previously undiagnosed individuals. If these endocrine disorders are not rapidly identified or if specific treatment is delayed, significant complications or even death may occur. Careful evaluation of clinical history and a high degree of suspicion are the corner stone to diagnose such problems. Aggressive management of the patient is equally important as the complications are devastating and can prove highly fatal. The present article is an attempt to review some of the common endocrine emergencies in intensive care unit and the challenges associated with their diagnosis and management. J MEDICINE July 2016; 17 (2) : 100-108